Applicability of Routine Targeted Next-generation Sequencing to Estimate Tumor Mutational Burden (TMB) in Patients Treated With Immune Checkpoint Inhibitor Therapy. Issue 2 (February 2020) - Pinato, David J.; Urus, Heather; Newsom-Davis, Thomas; Du Parcq, Persephone; Belessiotis, Katherine; Mapara, Leah; Gupta, Nandita; Power, Danielle; Weir, Justin; Wong, Ching Ngar; Ratnakumaran, Ragu P.; Dominy, Kathy; et al.
Abstract : It remains unclear whether targeted next-generation sequencing (tNGS) conveys a reliable estimate of tumor mutational burden (TMB). We sequenced 79 archival samples of immune checkpoint inhibitors (ICPIs) recipients (57% lung cancer, 43% melanoma) using Ion Ampliseq Cancer Hotspot Panel. Employing multiple cutoff values, we verified that TMB by tNGS did not correlate with response or survival following ICPI. We found enrichment of ATM mutations in ICPI-refractory tumors ( P =0.01) to correlate with worse survival (4.2 vs. 10 mo, P =0.03). Limited-coverage tNGS delivers an imprecise estimate of patients' TMB but may aid identification of candidate somatic variants of predictive/prognostic significance.